Superior Vena Cava Syndrome and Hypoxic Ischemic Encephalopathy Secondary to a Massive, Right-Sided Immature Cervical Teratoma. (April 2020) - Goldstein, Nicolas PN; Zhang, Xin; Sollinger, Christina; Chaturvedi, Apeksha; Turri, Riki; Mehta, Rupal; Metlay, Leon A; Katzman, Philip J
Cervical teratomas are a rare form of fetal teratoma that can grow to massive size. Generally, these masses can be surgically excised after birth with excellent physical and functional prognosis because the benign variants respect anatomical borders. The primary complications of these masses are associated with compromise of the trachea and esophagus: upper airway obstruction and polyhydramnios. We report the first documented occurrence of superior vena cava syndrome and hypoxic ischemic encephalopathy associated with a massive, right-sided cervical teratoma. This case highlights that when cervical teratomas are right-sided and sufficiently large, they can extend inferiorly and compromise central venous return to the heart. This unique presentation would likely have required fetal surgical excision to avoid catastrophic cerebral injury.